2020
DOI: 10.3389/fimmu.2020.00096
|View full text |Cite|
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Modulates the Antiviral Response of Bronchial Epithelial Cells

Abstract: Cystic fibrosis (CF) patients frequently acquire Pseudomonas aeruginosa infections that have been associated with a bad prognosis and an increased rate of pulmonary exacerbations. Respiratory viruses can cause exacerbations in chronic pulmonary diseases including COPD or asthma and have been suggested to contribute to exacerbations also in CF. In this study we investigated a possible link between P. aeruginosa infection and susceptibility to respiratory viruses. We show that P. aeruginosa is able to block the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 68 publications
3
12
0
Order By: Relevance
“…Our results also demonstrated that the enhanced mICAM-1 response was primarily attributable to the loss of LasR-regulated proteases that degraded ICAM-1, findings which are consistent with previous reports by our group and others that LasR-regulated proteases can degrade mediators of the innate immune system and the complement system [23,[46][47][48]54,69]. Furthermore, proteolytic cleavage of mICAM-1 by host-proteases such as neutrophil elastase and cathepsin G has been described [70,71], and degradation by bacterial proteases has been considered a potential mechanism of bacterial virulence [72].…”
Section: Plos Pathogenssupporting
confidence: 93%
See 3 more Smart Citations
“…Our results also demonstrated that the enhanced mICAM-1 response was primarily attributable to the loss of LasR-regulated proteases that degraded ICAM-1, findings which are consistent with previous reports by our group and others that LasR-regulated proteases can degrade mediators of the innate immune system and the complement system [23,[46][47][48]54,69]. Furthermore, proteolytic cleavage of mICAM-1 by host-proteases such as neutrophil elastase and cathepsin G has been described [70,71], and degradation by bacterial proteases has been considered a potential mechanism of bacterial virulence [72].…”
Section: Plos Pathogenssupporting
confidence: 93%
“…LasR regulates the expression of several secreted proteases such as AprA, LasA, LasB and type IV protease (T4P) that can degrade components of host defenses and immunity [ 23 , 46 48 ], some of which have been shown to be heat-labile [ 23 , 49 ]. Therefore, we hypothesized that the loss of mICAM-1 protein signal upon stimulation with wild-type filtrates was due to the activity of these proteases, and sought to characterize the proteolytic activity in wild-type and lasR mutant filtrates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings indicate that next to genetic differences, IL-6 degradation might also be affected by viral infection of the host cell. PA proteases have previously been described to also target CXCL-8 (LaFayette et al, 2015;Saint-Criq et al, 2018) and IFN-l (Sorensen et al, 2020). In our model, we found the effects of coinfection with PA and HRV16 on CXCL-8 to be similar to those of HRV infection alone.…”
Section: Discussionsupporting
confidence: 75%